TINJAUAN PUSTAKA KARAKTERISASI DAN POTENSI PEMANFAATAN FLY ASH DAN BOTTOM ASH (FABA): REVIEW ON CHARACTERIZATION AND UTILIZATION POTENTIAL OF FLY ASH AND BOTTOM ASH (FABA) - Ferian Anggara; Himawan T.B.M Petrus; Dea Anisa Ayu Besari; Hotden Manurung; Febry Yulindra Abdi Saputra (Buletin Sumber Daya Geologi, 2021)
Fly ash and bottom ash (FABA) is defined as waste residu that is produced from coal combustion process in electric power plant. Its production will increase due to high demand of electric energy. It commonly consists of silica, alumina, ferric oxide, and others oxide. Coal ash is also an economically promising resource for extraction of several valuable elements, including Ge, Ga, rare earth elements and yttrium (REY), Nb, Zr, V, Re, Au, Ag, and base metals such as Al. Physical and chemical characteristics of FABA are important because it will affect their option of re-use and disposal method. Other potential utilization for FABA was involved geotechnical applications such as geopolymer material. Cenospheres are one of the most valuable materials found in FABA. To increase the potential use of FABA, many separation techniques have been developed to extract the value-added components, including: cenospheres, valuable metal and trace elements such as rare earth element and yttrium (REY), also the unburned carbon.